A new method for heat integration between nonrepeatable batches. Issue 3 (5th March 2021) - Anastasovski, Aleksandar
Abstract: Heat storage is an important part for heat integration between nonrepeatable batches. This article suggests a new approach in the design of heat storage exchange network for heat integration between nonrepeatable batches. This approach is built on the TRANSSHIPMENT method. The main idea is reusing the waste heat from stream segments that are designed to exchange heat with utilities. These extracted stream segments are added to every upcoming time slice as new energy streams. The possible heat exchange between extracted segments and existing streams in every Time Slice is based on the suggested algorithm which includes the main rules of the Pinch technology. All possible matches are potential heat storage units or subsystems. The efficiency of heat recovery increases if the schedule of nonrepeatable batches is repeated every day. That makes a great impact on the production costs. Otherwise, as it is in the given case study, the waste heat reduction is small and cannot support the investment for the solution. The reduction of hot utility in the presented case study is 43.5% and the reduction of cold utility is 12.1% in the start‐up period of the plant (58.94 hours).